2023
DOI: 10.1021/jacs.2c10915
|View full text |Cite
|
Sign up to set email alerts
|

Triangulating Dopant-Level Mn(II) Insertion in a Cs2NaBiCl6Double Perovskite Using Magnetic Resonance Spectroscopy

Abstract: Lead-free metal halide double perovskites are gaining increasing attention for optoelectronic applications. Specifically, doping metal halide double perovskites using transition metals enables broadband tailorability of the optical bandgap for these emerging semiconducting materials. One candidate material is Mn(II)-doped Cs 2 NaBiCl 6 , but the nature of Mn(II) insertion on chemical structure is poorly understood due to low Mn loading. It is critical to determine the atomic-level structure at the site of Mn(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Finally, the 119 Sn NMR linewidths for all cation-substituted materials (K, Rb, and Cs) increase as the halogen atoms are exchanged from Cl → Br → I. This increase in linewidth is likely due to J -coupling between 119 Sn and the directly bonded halogens that has been reported in similar materials. …”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Finally, the 119 Sn NMR linewidths for all cation-substituted materials (K, Rb, and Cs) increase as the halogen atoms are exchanged from Cl → Br → I. This increase in linewidth is likely due to J -coupling between 119 Sn and the directly bonded halogens that has been reported in similar materials. …”
Section: Resultsmentioning
confidence: 61%
“…4.5 kHz with a lineshape indicating the presence of CSA. Upon slow MAS ( v r = 5 kHz) (Figure b), a second-order quadrupolar lineshape emerges, which is indicative of perturbation of the local electric field gradient (EFG) about the A-site. , To extract the experimental quadrupolar and CSA parameters for 39 K in K 2 SnBr 6 , the nonspinning and MAS spectra were first fit using the parameters predicted by periodic DFT computations. The predicted quadrupole coupling constant ( C Q ) and asymmetry parameter (η) are 0.77 MHz and 0.54, respectively, while the CSA is predicted to have Ω = 26 ppm and κ = −0.02.…”
Section: Resultsmentioning
confidence: 99%
“…Although challenging, 209 Bi NMR is gaining attention as a sensitive method to probe solids 71 , 72 . For example, in double perovskites, it has been used to examine ion substitution in Mn-Cs 2 NaBiCl 6 73 , Cs 2 (Bi 1– x In x )AgCl 6 74 , and Cs 2 AgBiBr 6 75 ; in these cases, the [BiX 6 ] 3− octahedra are rather symmetrical, which limits the broadening induced by quadrupolar coupling. The 15% Bi-substituted sample was chosen for study because it offers the highest sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Karmakar et al realized Mn 2+ doping in CNBC in the presence of concentrated HCl solvent at 120 °C. 34 Yao et al have reported a colloidal synthetic approach for Ag-, Mn- and Er-doped CNBC nanocrystals by reacting the corresponding metal acetate precursors with trimethylsilyl chloride under a nitrogen atmosphere at 230 °C. 35 However, most of the previous synthetic approaches for ion-doped CNBC usually involved organic ligands, relatively complicated procedures, or harsh conditions ( e.g.…”
Section: Introductionmentioning
confidence: 99%